Criminological Outlook of Overcoming Disproportionate Punishment in Environmental Crimes - Ali, Mahrus; Tahir, Ach; Faisal; Irnawati; Pujiyono; Arief, Barda Nawawi (International Journal of Criminology and Sociology, 2021)
Criminal determination in a number of environmental offenses still raises excessive criminal threats. The weight of a criminal for offense committed due to negligence is even more severe than the weight of the criminal for deliberate offense which causes death. Criminal weights can also not be compared in weight to offenses that have the same level of seriousness. In the Law reviewed, the criminal threat in some formal offenses is more severe than in material offenses so that it violates the principle of proportionality. Excessive crimes can be overcome through ranking offenses based on their seriousness which refers to the four models of criminalization based on environmental losses. The serious environmental pollution model places the most serious offense ranking, followed by the concrete harm model, then the concrete endangerment, and finally the abstract endangerment. After the ranking of environmental offenses is compiled, the criminal weight is determined. Spacing of penalties between the offense groups to another also needs to be determined.